2023
DOI: 10.1152/jn.00085.2023
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of neuromuscular electrical stimulation on cortical dynamics and reflex activation

Abstract: Superimposing neuromuscular electrical stimulation (NMES) on voluntary muscle contractions has shown the potential to improve motor performance even more than voluntary exercise alone. Nevertheless, the neurophysiological and neurocognitive mechanisms underlying this technique are still unclear. The aim of this study was to investigate the acute responses in spinal excitability, and brain activity following three conditions: NMES superimposed on isometric contractions (NMES+ISO), passive NMES, and voluntary is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Participants were allowed a recovery period of 10 min between all conditions. The number and duration of contractions used in this protocol was selected to prevent development of muscle fatigue ( Gueugneau et al, 2017 ; Grosprêtre et al, 2018 ), while at the same time inducing neural adjustments as demonstrated in previous literature ( Lagerquist et al, 2012 ; Borzuola et al, 2020 ; Borzuola et al, 2023 ). All the procedures were performed on participants’ dominant leg as described by Botter et al (2011) .…”
Section: Methodsmentioning
confidence: 99%
“…Participants were allowed a recovery period of 10 min between all conditions. The number and duration of contractions used in this protocol was selected to prevent development of muscle fatigue ( Gueugneau et al, 2017 ; Grosprêtre et al, 2018 ), while at the same time inducing neural adjustments as demonstrated in previous literature ( Lagerquist et al, 2012 ; Borzuola et al, 2020 ; Borzuola et al, 2023 ). All the procedures were performed on participants’ dominant leg as described by Botter et al (2011) .…”
Section: Methodsmentioning
confidence: 99%
“…During each experimental condition, a target force of 20% of MVIC was set based on MVIC measurements. Previous studies involving the application of NMES demonstrated that this force level could affect spinal excitability without inducing muscle fatigue [39][40][41][42]48,58]. In this regard, MVIC was evaluated again at the end of the whole experimental session to determine if muscle fatigue had arisen.…”
Section: Participantsmentioning
confidence: 99%
“…According to previous studies [39,41,56], the stimulus intensity was selected to evoke an H-reflex (H test ) on the ascending limb of the RC with an amplitude corresponding to 80-85% of the Hmax, as illustrated in Figure 4. To ensure stimulus consistency and repeatability, a small M-wave (M test ) corresponding to the H test was selected and monitored throughout the entire experiment [39,40]. If the M-wave amplitude lay within 5% of the selected M test , the corresponding H-reflex measure was accepted.…”
Section: Soleus H-reflexmentioning
confidence: 99%
See 2 more Smart Citations